2018
DOI: 10.1111/opo.12439
|View full text |Cite
|
Sign up to set email alerts
|

Detecting glaucomatous progression with infrequent visual field testing

Abstract: Infrequent visual field testing does not dramatically alter predictive values at 2 years, but does substantially delay when significant progression may first be detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“… 7 The next issue is whether the benefits of frontloading may be further enhanced by shortening the follow-up interval, such as was suggested by Wu et al 21 The most notable benefit of shortening the follow-up interval from 2 years to 6 months was the much less severe mean deviation loss measured at the case detection visit, similar to the results found by Anderson and colleagues. 32 Thus, clinicians should be cognizant of the expected mean deviation result at the end of the follow-up interval they use.…”
Section: Discussionmentioning
confidence: 99%
“… 7 The next issue is whether the benefits of frontloading may be further enhanced by shortening the follow-up interval, such as was suggested by Wu et al 21 The most notable benefit of shortening the follow-up interval from 2 years to 6 months was the much less severe mean deviation loss measured at the case detection visit, similar to the results found by Anderson and colleagues. 32 Thus, clinicians should be cognizant of the expected mean deviation result at the end of the follow-up interval they use.…”
Section: Discussionmentioning
confidence: 99%
“…How many perimetric tests should be administered to the patient per year? Using a simulation method, Anderson and colleagues [39] showed that the predictive values of annual visual fields at 2 years were slightly worse than those obtained using six visual fields. In other words, reduced test frequency (one per year) does not substantially alter the prediction of progression computed with a higher (namely six) numbers of examinations at 2 years.…”
Section: The Question Now Is: What Promotes the Functional Loss Progression In Glaucoma?mentioning
confidence: 99%
“…A study found the time to detect rapid progression (defined as mean deviation change of 2 dB/year) was 1.7 years with triannual testing versus 5 years with annual testing [18]. Compared with triannual testing in the first 2 years, annual testing in the first 2 years was associated with delayed detection of visual field progression, though the positive-predictive and negative-predictive values of individual fields were unaffected [19]. Frontloading visual fields (two visual fields per visit, per 6 months) has been proposed as an approach to overcome challenges associated with obtaining multiple sets of perimetry data; compared with annual testing, frontloading achieved earlier detection and reduced mean deviation change prior to detecting visual field progression [20 ▪ ,21 ▪ ].…”
Section: Repeat Testingmentioning
confidence: 99%